The Phenomenon of using the “Bumble” App in Friends with Benefits Relationships - Dimas Zuanfaizin Pamungkas; Siti Khumayah; Aghnia Dian Lestari (Apollo: Journal of Tourism and Business, 2025)
Friends With Benefits is a relationship that is becoming more and more common with the advances of technology and online dating these days, such as the Bumble dating app. These applications have led to a new phenomenon called Friends With Benefits (FWB) situations. The commitment free and unbureaucratic nature of these types of apps form casual liaisons without emotional ties, thus ultimately possibly leading to problems with varied expectations. In this paper we focus on the problems, dynamics, and conflicts that are prone to emerge in FWBs started via the Bumble app. Method This study adopts a qualitative, case study research method with data from semi-structured interviews with five informants who have had FWB relationships using the Bumble app. The findings may offer insights into how FWB relationships are initiated, maintained and terminated in the era of social media and contemporary social relations. As information is given, the participants reveal themselves before moving into Orientation, Effective Exchange and finally Stable Exchange. The restriction in FWB arrangements is that freedom, since not all couples have the freedom.